(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2022)
We conducted an inventory in the wilaya of Batna more particularly the region of Timgad during the period from January 2018 to December of the same year. Sampling is done monthly using the “Dipping” method to collect the mosquito larvae which were then transported to the laboratory for identification. Five mosquito species were collected in the surveyed site presented by 1035 individuals, these were Culex pipiens, Culex theileri, Culex hortensis, Culex deserticola and Culiseta longiareolata which appears to be the most abundant with three significant pullulation peaks. This inventory is supplemented by a physicochemical analysis of water to study the correlation between mosquito larval density and site water quality. J. Biodivers. Conserv. Bioresour. Manag. 2022, 8(1): 49-56